High-whiteness and low-titanium-dioxide-content efficient light-blocking master batch and preparation method thereof

By using a combination of styrene-methyl methacrylate copolymer resin and thermoplastic high polymer material in high-light blocking masterbatch, combining interface effect and microcylindrical cell structure, the problem of excessive titanium dioxide content is solved and high Whiteness, low titanium dioxide content and high light barrier properties, and reduce production energy consumption and cost.

CN119463376AActive Publication Date: 2025-02-18SHANGHAI HANHUI NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411509981.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The titanium dioxide content in the existing high-light blocking masterbatches is too high, resulting in low whiteness, high cost and environmental protection problems. In addition, traditional polyester plastic packaging has high light transmittance, which cannot meet the high-light blocking needs of dairy products.

Method used

Using a combination of styrene-methyl methacrylate copolymer resin, thermoplastic high polymer material and titanium dioxide, the light barrier performance is improved through interface effects and micro-cell structure, and the titanium dioxide content and energy consumption are reduced through optimization formulation and processing technology. .

Benefits of technology

It achieves high whiteness, low titanium dioxide content and high light barrier properties, reduces the energy consumption of injection and blowing bottles, improves the toughness and physical properties of the bottle body, and has a lower cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463376A_ABST
    Figure CN119463376A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient light-blocking master batch with high whiteness and low titanium dioxide content and a preparation method of the efficient light-blocking master batch. Styrene-methyl methacrylate copolymer resin is selected as a basic carrier; after the styrene-methyl methacrylate copolymer resin and the polyester plastic are blended and injected into a blank, an uneven and irregular interface effect is formed in a bottle blowing and stretching process, so that light rays are scattered, refracted and reflected, the transmittance of the light rays is reduced, and a synergistic light blocking effect is achieved; in order to maximize the interfacial effect, in addition to the styrene-methyl methacrylate copolymer, a high polymer which also has a certain interfacial effect with the polyester plastic is also added; meanwhile, a compatilizer or a grafting agent is added to improve the compatibility of the polymer and the polyester plastic; under the same addition proportion, the light-blocking master batch disclosed by the invention has higher whiteness and light-blocking property and lower titanium dioxide content, the energy consumption of blank injection and bottle blowing can be obviously reduced, and a bottle body is more excellent in physical property, better in toughness effect and lower in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic coloring, and in particular to a high-whiteness, low-titanium dioxide content, high-efficiency light-blocking masterbatch and a preparation method thereof. Background Art

[0002] When it comes to dairy product packaging, including milk drinks or yogurt packaging, light protection is one of the factors that need to be considered. Light has a significant impact on dairy products. Light can destroy the nutrients in milk, stimulate unstable substances in milk to produce free radicals, and thus accelerate the oxidation and deterioration of milk. At the same time, many nutrients in milk, such as vitamin A, vitamin B2 (riboflavin), vitamin D, and amino acids, will be lost due to light. The most common reaction of milk under light conditions is the oxidation reaction of cysteine ​​triggered by light, which will generate sulfides such as mercaptans and dimethyl sulfide, all of which will seriously affect the taste and nutrition of milk.

[0003] At present, many dairy products are packaged and sold in cold chain, but the short shelf life, high storage and transportation costs, and narrow sales radius have seriously affected the sales scope and sales volume; there are also dairy companies that use Tetra Pak paper and plastic packaging for room temperature sales after high temperature sterilization, and the shelf life can be extended to half a year or even 9 months, and the sales scope can be expanded to the whole country, but Tetra Pak packaging has problems such as large equipment investment, single packaging specifications, and no way to reseal once opened, and it is difficult to recycle and reuse. Room temperature plastic packaging is increasingly favored by dairy companies and consumers, among which polyester plastic packaging is the most popular. Polyester packaging has its unique advantages: diversified bottle design, high production efficiency, universal injection molding processing equipment, and avoidance of repeated investment. However, polyester plastic packaging has the characteristics of high light transmittance, which is contrary to the requirement of high light blocking for dairy products. Therefore, it is necessary to add high light blocking masterbatch (the light blocking is preferably above 99.9%) to improve the light blocking performance of polyester packaging bottles, thereby protecting the quality of dairy products and extending the shelf life.

[0004] my country's annual dairy output is 30.546 million tons (National Bureau of Statistics, full-year data for 2023). For such a huge dairy market, cold chain transportation and Tetra Pak paper and plastic packaging can no longer meet the needs of market expansion and consumers' growing pursuit of packaging diversity, aesthetics and high quality. Room temperature plastic packaging has emerged, and high light-blocking additives for plastic packaging have also emerged.

[0005] The mainstream high-light-blocking masterbatch on the market is basically based on polyester materials as the carrier, combined with other polymers with stronger toughness, such as polypropylene PP (Polypropylene), polyethylene PE (Polyethylene), polystyrene PS (Polystyrene) and other polymer materials. These materials are not only compatible with polyester plastics, but also can improve the degree of integration with inorganic substances such as titanium dioxide to a certain extent, thereby improving the light-blocking performance, and can also improve the toughness and impact resistance of the bottle body when the light-blocking masterbatch is added at a high ratio, avoiding problems such as the bottle body falling and bursting. These traditional high-light-blocking masterbatches are mainly based on titanium dioxide in the light-blocking part, and the content in the formula is as high as 60% to 70%. Because titanium dioxide has the advantages of high whiteness and good hiding power, in order to improve the hiding power, inorganic substances with better hiding power such as carbon black are sometimes added. However, these traditional high-light-blocking masterbatches have problems such as low whiteness, high titanium dioxide content, high bottle blowing energy consumption, and high bottle explosion rate. The gray appearance of the bottle lowers the texture and aesthetics of the packaging. The outside of the bottle usually needs to be completely wrapped with a label to cover the quality defects of the appearance, but the mouth of the bottle will still be exposed after opening the lid, affecting the sensory experience of consumers; Regarding titanium dioxide, on May 6, 2021, the European Food Safety Authority (EFSA) announced that the genotoxicity of titanium dioxide (TiO2; CAS13463-67-7) could not be ruled out, so the EU announced a ban on titanium dioxide as a food additive. Although on November 23, 2022, the European Court of Justice recommended the abolition of the classification and labeling of titanium dioxide as a carcinogen in the form of inhaled certain powders, which means that the EU is currently loosening the application of titanium dioxide in the food, coatings and other industries, detailed guidelines for the inhalation and packaging applications of titanium dioxide may still be issued in the future. It can be seen that the content or addition ratio of titanium dioxide used in food and beverage packaging should also be controlled as much as possible to minimize the risk of its migration into food and beverages.

[0006] In summary, there is a strong demand in the market for high-light-blocking masterbatches with high whiteness, low titanium dioxide content, energy saving and high efficiency. Summary of the invention

[0007] The purpose of the present invention is to provide a high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch and a preparation method thereof, so as to solve the problem of excessively high titanium dioxide content in the high-light-blocking masterbatch.

[0008] In order to achieve the above-mentioned purpose of the invention, the present invention provides a high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch, comprising:

[0009] Styrene-methyl methacrylate copolymer resin, thermoplastic polymer material and titanium dioxide;

[0010] The mass content of the styrene-methyl methacrylate copolymer resin is 5% to 60%, the mass content of the thermoplastic high polymer material is 3% to 30%, and the mass content of the titanium dioxide is 10% to 60%;

[0011] The thermoplastic high polymer material includes: one or more of thermoplastic elastomer TPE, polymethyl methacrylate PMMA, poly-4-methyl-1-pentene PMP, cycloolefin copolymer COC, thermoplastic polyester elastomer TPEE or aliphatic polyketone resin POK.

[0012] Optionally, it also includes a high-hiding inorganic substance with a mass content of 1% to 30%, and the high-hiding inorganic substance includes one or more of calcined kaolin, calcite powder, silica powder, zinc oxide, barium sulfate, zinc sulfide or calcium carbonate.

[0013] Optionally, the invention further comprises a metal pigment with a mass content of 0.01% to 5%, wherein the metal pigment comprises a metal aluminum pigment or a bronze pigment.

[0014] Optionally, the composition further comprises a compatibilizer having a mass content of 0.01% to 5%, wherein the compatibilizer comprises one or more of POE-g-GMA, PP-g-MAH, PE-g-MAH or POE-g-MAH.

[0015] Optionally, the invention further comprises an auxiliary agent with a mass content of 0.01% to 10%, wherein the auxiliary agent comprises one or more of a dispersing lubricant, an antioxidant, a reheat absorber, a light stabilizer or an antistatic agent.

[0016] Optionally, the composition further comprises an organic dye having a mass content of 0.01% to 10%.

[0017] The present invention also provides a method for preparing a high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch, comprising:

[0018] Disperse the formulated materials into a uniform mixture and granulate;

[0019] The granulation process comprises:

[0020] The mixture is heated to the plasticizing temperature and vacuumed;

[0021] Passing the plasticized material through an extruder to form a continuous molten extrudate;

[0022] Cooling to form solid particles;

[0023] The solid particles are cut into predetermined sizes and then screened and discarded.

[0024] Optionally, during the granulation process, the feed temperature section is set at 280°C to 290°C, the equilibrium temperature section is set at 270°C to 280°C, and the discharge temperature section is set at 260°C to 270°C.

[0025] Optionally, during the granulation process, the vacuum degree of the vacuum pumping section is controlled to be 0.6-0.8 MPa; the temperature of the extrusion section is 260° C.; and the speed of the pelletizer is 800-900 r / min.

[0026] Compared with the prior art, the advantages and positive effects of the present invention are as follows: the present invention provides a high-light-blocking masterbatch with high whiteness, low titanium dioxide content and energy saving and consumption reduction. Compared with traditional high-light-blocking masterbatch, at the same addition ratio, it has higher whiteness and light-blocking properties, lower titanium dioxide content, and significantly reduced energy consumption for injection molding and bottle blowing. In addition, the physical properties of the bottle body are better, the toughness effect is better, and the cost is lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the molecular structure of styrene-methylmethacrylate copolymer resin (MS) in an embodiment of the present invention;

[0028] Figure 2 It is the infrared spectrum of MS in the embodiment of the present invention;

[0029] Figure 3 Schematic diagram of the formation process of MS resin in an embodiment of the present invention;

[0030] Figure 4 This is a comparison curve of hiding power of different pigments;

[0031] Figure 5 Schematic diagram of the interfacial effect and microcellular structure of MS and polyester blends in an embodiment of the present invention;

[0032] Figure 6 Schematic diagram of the interfacial effect and microcellular pore structure of the blend of inorganic substances such as MS, polyester and titanium dioxide in the embodiment of the present invention;

[0033] Figure 7 This is a bar graph of the light-blocking properties of the compositions of each group F2-F7 in the embodiments of the present invention;

[0034] Figure 8 This is a bar graph of the light-blocking properties of each group of compositions F8-F15 in the embodiments of the present invention;

[0035] Fig. 9 It is a bar graph of light-blocking properties of each group of compositions F16-F25 in the embodiments of the present invention;

[0036] Fig.10This is an electron microscope scanning image of the composition of group F23 in the embodiment of the present invention;

[0037] Fig.11 This is a bar chart comparing the whiteness of Experimental Examples 1-9 and the traditional light-blocking masterbatch in the embodiments of the present invention;

[0038] Fig.12 Schematic diagram showing the comparison of light-blocking performance between Experimental Examples 1-9 and conventional light-blocking masterbatches in the embodiments of the present invention;

[0039] Fig.13 Schematic diagram of vertical pressure loading of a conventional empty bottle of light-blocking masterbatch in an embodiment of the present invention;

[0040] Fig.14 Schematic diagram of vertical pressure loading of empty bottles in Experimental Example 2 of the embodiment of the present invention. DETAILED DESCRIPTION

[0041] The present invention will be described in more detail below in conjunction with the accompanying drawings, wherein preferred embodiments of the present invention are shown, and it should be understood that those skilled in the art may modify the present invention described herein and still achieve the beneficial effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art and not as a limitation of the present invention.

[0042] The present invention is described in more detail in the following paragraphs by way of example with reference to the accompanying drawings. The advantages and features of the present invention will become more apparent from the following description. It should be noted that the accompanying drawings are in very simplified form and are not in exact proportions, and are only used to facilitate and clearly assist in illustrating the purpose of the embodiments of the present invention.

[0043] Embodiment 1

[0044] In this embodiment, a high-whiteness, low-titanium dioxide content, high-efficiency light-blocking masterbatch is provided, comprising: styrene-methyl methacrylate copolymer resin, a thermoplastic high polymer material and titanium dioxide; the mass content of the styrene-methyl methacrylate copolymer resin is 5% to 60%, the mass content of the thermoplastic high polymer material is 3% to 30%, and the mass content of the titanium dioxide is 10% to 60%.

[0045] The mass content of the styrene-methyl methacrylate copolymer resin can specifically be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0046] The mass content of the titanium dioxide can specifically be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0047] The mass content of the thermoplastic high polymer material can specifically be 5%, 10%, 15%, 17%, 18%, 19%, 20%, 22%, 24%, 25%, 26%, 28%, 29% or 30%.

[0048] Styrene-methylmethacrylate copolymer (MS), please refer to the molecular structure and infrared spectrum of MS resin Figure 1 - Figure 2 .

[0049] Styrene-methyl methacrylate copolymer (MS) resin has the good processing fluidity and low hygroscopicity of polystyrene, as well as the weather resistance and excellent optical properties of methyl methacrylate. Its refractive index is 1.56, and its transparency is similar to that of polystyrene. It is a transparent, non-toxic thermoplastic. The impact strength of MS resin is higher than that of polystyrene, and its heat deformation temperature is similar to that of methyl methacrylate. It is an optical grade material with a series of excellent properties.

[0050] For the formation process of styrene-methyl methacrylate copolymer (MS) resin, please refer to Figure 3 .

[0051] Styrene-methyl methacrylate copolymer (MS) resin is a silane-terminated polyether prepolymer, which is mainly formed by copolymerization of MMA monomer and styrene. It has excellent optical properties and is widely used in optical display, daily necessities, medical and other fields due to its non-toxicity, good fluidity, weather resistance, low hygroscopicity and other characteristics. my country's MS production capacity is gradually increasing, and many companies have made layouts in this field, such as Suzhou Shuangxiang Optics, Yantai Wanhua, Jiangsu Saibaolong, Jiangsu Xinpu, Henan Duonaibao and other companies, making the supply of MS gradually sufficient and the price of MS products return to a rational level.

[0052] The reason why the present invention chooses styrene-methyl methacrylate copolymer as the basic carrier is mainly because it forms an uneven and irregular interface effect during the blowing and stretching process after being blended with polyester plastic, which scatters, refracts and reflects light, reduces the transmittance of light, and thus achieves a synergistic light-blocking effect.

[0053] The so-called interface effect refers to the changes in physical, chemical and biological properties caused by the special properties of the surface or interface of the material, which can affect the performance and behavior of the material. This application is mainly reflected in the optical influence of the interface effect: light is reflected, refracted and scattered on the surface or interface of two materials, thereby affecting the light transmittance or hiding power of the material.

[0054] At the same polymer addition ratio, in order to maximize the interfacial effect, in addition to styrene-methyl methacrylate copolymer, a polymer material that also has a certain interfacial effect with polyester plastic is added, such as thermoplastic elastomer TPE (Thermoplastic Elastomer), polymethyl methacrylate PMMA (Polymethyl Methacrylate), poly-4-methyl-1-pentene PMP (Poly(4-methyl-1-pentene)), cycloolefin copolymer COC, thermoplastic polyester elastomer TPEE (Thermoplastic Polyester Elastomer) or aliphatic polyketone POK resin. One or more of them can enhance the interfacial effects produced by several different polymers.

[0055] Experiments have shown that by adding another suitable polymer in an appropriate ratio, the light-blocking performance and injection molding blow molding processing performance can be improved to a certain extent, and the overall cost can also be reduced.

[0056] The applicant has found that when polymers such as styrene-methyl methacrylate copolymer MS, thermoplastic elastomer TPE, polymethyl methacrylate PMMA, poly-4-methyl-1-pentene PMP, cycloolefin copolymer COC, thermoplastic polyester elastomer TPEE, aliphatic polyketone (POK) resin are blended with polyester plastic, not only a certain degree of interfacial effect is produced, but also many tiny micropores are formed. This is because the blending of two or more polymers with different crystalline properties changes their crystal shape and reduces their crystallinity. The reduction in crystallinity increases the solubility of CO2, thereby generating many tiny microbubble pores. These tiny microbubble pore structures can also improve the light-blocking property or hiding power to a certain extent, because the light-blocking property depends not only on the concentration of inorganic pigments such as titanium dioxide, but also on the refractive index difference between the pigment and the medium. The larger the difference, the better the light-blocking property. If the refractive index of the pigment is kept unchanged and the refractive index of the medium is reduced, the light-blocking property of the bottle can be improved. Introducing micro-bubble structures in plastic sheets or bottles can reduce the refractive index of the medium. The more pores are introduced, the lower the refractive index of the porous medium. The greater the refractive index difference between the pigment and the medium, the better the light-blocking property of the bottle. However, too many and too dense micro-bubbles will also affect the toughness, strength and other key physical properties of the bottle, and may cause the bottle to break easily, so careful balance is required.

[0057] The light-blocking property of a pigment is also called hiding power, which is caused by the difference in refractive index between the pigment and the surrounding medium or base material. When the refractive index of the pigment and the base material is equal, it is transparent. When the refractive index of the pigment is greater than that of the base material, hiding occurs. The greater the difference between the two, the stronger the hiding power or light-blocking property. The refractive index data of several common substances are shown in Table 1 below.

[0058] Table 1

[0059]

[0060] White pigments are mainly scattered, and the hiding power generated by scattering is mainly related to three factors: Lorentz factor, pigment concentration and pigment particle size. The Lorentz factor reflects the refractive index relationship between the pigment and the base material, as shown in the following formula:

[0061] L=(n p 2 -n b 2 ) / (n p 2 +2n b 2 );

[0062] Where L is the Lorentz factor, n p is the refractive index of the pigment, n b is the refractive index of the film.

[0063] The light blocking property or hiding power is proportional to the square of L, which means that the greater the refractive index difference between the pigment and the base material, the higher the light blocking property or hiding power.

[0064] In order to verify the light-blocking property of different inorganic substances in PET polyester, PET polyester (Wankai WK-801) was first ground into 200-mesh fine powder, and then mixed with titanium dioxide (Chemours R-902), calcium carbonate (Omya OM2T), zinc oxide (Lutai LT-AH01), and calcined kaolin (BASF Translink37) at a ratio of 95% (PET polyester): 5% (inorganic pigment), and injection molded into sheets. The same thickness (0.3mm) was taken to test its different light transmittances. The comparison curves are shown in Figure 2. Figure 4 shown.

[0065] pass Figure 4 It can be seen that rutile titanium dioxide and polyester PET substrate have a higher refractive index, and thus have higher hiding power or light blocking properties.

[0066] Please refer to Figure 5 - Figure 6 In the two electron microscope photos, Figure 5 This is an electron microscope image of a blend of styrene-methyl methacrylate copolymer and polyester resin. Figure 6 This is a picture of the blend of styrene-methyl methacrylate copolymer, polyester, titanium dioxide and other inorganic substances. The interfacial effect and micro-bubble structure produced can be clearly seen.

[0067] In order to observe the superimposed light-blocking effect of polyester PET and the resin with interface effect of the present application, the mixture of the base resin part of Experimental Example 7 of the present application was used as the analysis sample, and its composition and proportion were shown in Table 2 below. The analysis sample was dried and mixed, and then injection-molded and blown into a bottle. A thin slice of a certain thickness was cut and scanned by an electron microscope (the electron microscope was CIQTEK SEM5000). Figure 5 shown.

[0068] Table 2

[0069]

[0070]

[0071] The formula raw material information and ratio of Experimental Example 7 are summarized in Table 3. After drying, the light-blocking masterbatch obtained in Experimental Example 7 is blended with 90% dried polyester PET (Zhejiang Wankai WK-801) at a ratio of 10%, and the masterbatch is scanned by an electron microscope to obtain an electron microscope photo as shown in Table 3. Figure 6 shown.

[0072] Table 3

[0073]

[0074] The main application direction of the present invention application is polyester resin, which includes polyethylene terephthalate (PET), copolymers of PET, polybutylene terephthalate (PBT), copolymers of PBT, polyethylene naphthalate (PEN), non-crystalline copolyester (PETG) and polyarylate (PAR), polylactic acid (PLA), polytrimethylene terephthalate (PTT), polyethylene furandicarboxylate (PEF), polycyclohexane dimethyl terephthalate (PCT), copolymers of PCT, polycaprolactone (PCL), polyhydroxyalkanoate (PHA) and copolymers of PHA, etc. According to the universality of the final application, bottle-grade polyester PET is usually the main application. Bottle-grade PET polyester is generally prepared by polycondensation of terephthalic acid (PTA) and ethylene glycol (EG) under the action of a catalyst such as antimony or titanium metal.

[0075] With polyester PET as the basic carrier, styrene-methyl methacrylate copolymer MS, thermoplastic elastomer TPE, polymethyl methacrylate PMMA, polymethylpentene PMP, cycloolefin copolymer COC, and aliphatic polyketone POK were prepared according to the proportions. All resins were purchased from the market, among which the polyester PET was Zhejiang Wankai bottle-grade polyester chips WK-801 with an intrinsic viscosity of 0.8dL / g; MS was Japan Electric Chemical TX400S; TPE was G2712 from GLS; PMP was TPX RT180 from Mitsui Chemicals; PMMA was IH830 from LG Chemicals; COC was Japan Polyplastics 6013S; POK was Korea Hyosung M630.

[0076] Seven mixture formulas were prepared according to the following ratios as shown in Table 4, wherein F1 in Table 4 is 100% PET resin, and F2-F7 each has 2% of different resins added in addition to 98% PET polyester. The light transmittance of these seven single or mixed materials was compared by making plates.

[0077] Table 4

[0078] F1 F2 F3 F4 F5 F6 F7 PET 100 98 98 98 98 98 98 MS 2 TPE 2 PMP 2 COC 2 PMMA 2 POK 2 100 100 100 100 100 100 100

[0079] For the above 7 kinds of mixture formulas, preforms were blown into bottles, and slices of about 2.5 cm×5 cm with a thickness of 2 mm were cut and tested with a spectrophotometer. To ensure the accuracy of the test data, a spectrophotometer with an integrating sphere was used in this embodiment.

[0080] The instrument used for detection in this embodiment is a Shimadzu spectrophotometer UV-2600i with an integrating sphere. The light transmittance at 650nm visible light is collected for comparison. The resulting bar graph is as follows: Figure 7 As shown in Table 5, the test data is compared:

[0081] Table 5

[0082] Light blocking performance F1 F2 F3 F4 F5 F6 F7 Light transmittance 91.03% 20.58% 27.15% 22.64% 21.89% 24.18% 20.83%

[0083] Depend on Figure 7 From the data in Table 5, it can be seen that after adding 2% of resins with different stretching ratios or interface effects: styrene-methyl methacrylate copolymer MS, thermoplastic elastomer TPE, polymethyl methacrylate PMMA, polymethylpentene PMP, cycloolefin copolymer COC or aliphatic polyketone (POK), the above resins are blended with polyester PET to produce different degrees of interfacial light-blocking properties, thereby improving the light-shielding property of the bottle, especially the interfacial light-blocking performance of styrene-methyl methacrylate copolymer MS is significantly more prominent.

[0084] Furthermore, pure polyester PET F1 is used as a reference sample, and then 92 parts of polyester PET is used as a basic carrier, and 8 parts of different resin mixtures are mixed, the resin mixture includes: styrene-methyl methacrylate copolymer MS, thermoplastic elastomer TPE, polymethylpentene PMP, cycloolefin copolymer COC, polymethyl methacrylate PMMA, and aliphatic polyketone (POK).

[0085] All mixed materials were purchased from the market, including Zhejiang Wankai bottle-grade polyester chips WK-801 with an intrinsic viscosity of 0.8dL / g; MS was TX400S from Japan Electric Chemical; TPE was G2712 from GLS; PMP was TPXRT180 from Mitsui Chemicals; COC was Polyplastics 6013S from Japan; PMMA was IH830 from LG Chemical; and POK was Hyosung M630 from South Korea.

[0086] Nine different mixed materials were prepared according to the following proportions, as shown in Table 6:

[0087] Table 6

[0088]

[0089] The 9 mixed materials in Table 6 were injection molded into sheets, and 2.5 cm × 5 cm thin sheets with a thickness of 2 mm were cut and tested with a spectrophotometer (Shimadzu UV-2600i). For transmittance data, please refer to Figure 8 shown.

[0090] Depend on Figure 8 From the data, we can see that after adding styrene-methyl methacrylate copolymer MS or a compound mixture of MS and thermoplastic elastomer TPE, polymethyl methacrylate PMMA, polymethylpentene PMP, cycloolefin copolymer COC, aliphatic polyketone (POK) and other resins, blending with polyester PET produces different degrees of interfacial light-blocking properties, thereby improving the light-shielding property of the bottle. Among them, the light-blocking property of the mixture of styrene-methyl methacrylate copolymer MS and several other resins with the same proportion is significantly more prominent than that of the mixture of styrene-methyl methacrylate copolymer MS with the same proportion. For example, compared with F8 and F9, the light transmittance of F8 is higher than that of F9.

[0091] Furthermore, taking the mixing of styrene-methyl methacrylate copolymer MS and aliphatic polyketone (POK) in different ratios as an example, when the ratio of MS:POK is 6:2, the light blocking performance is better than that of the ratio of 4:4 or 3:5, that is, the light transmittance of F14 is lower than that of F13 and F15.

[0092] It can be seen that the appropriate ratio of different interface effect resins has a great influence on the improvement of light blocking properties.

[0093] Furthermore, based on Table 6 and Figure 8 The test results are aimed at two questions: Does a polymer mixture with two appropriately proportioned materials based on a more obvious interface effect MS have better light blocking performance than any other mixture of two resins with interface effect? ​​Does the more interface effect resins are mixed, the better the light blocking performance? The applicant conducted the following test cases, in which the material manufacturers and grades in F16-F25 are exactly the same as those in F1-F15, such as material manufacturers, grades, drying, weighing, etc. The proportions of F16-F25 are shown in Table 7:

[0094] Table 7

[0095] F16 F17 F18 F19 F20 F21 F22 F23 F24 F25 PET 92 92 92 92 92 92 92 92 92 92 MS 4 3.5 5 6 TPE 4 4 2 2 PMP 4 4 1.5 COC 4 1 PMMA 4 4 4 1 1 POK 4 4 4 4 2 1 1 1 100 100 100 100 100 100 100 100 100 100

[0096] The 10 mixed materials of F16-F25 were injection molded into sheets, and 2.5 cm × 5 cm thin sheets with a thickness of 2 mm were cut and tested with a spectrophotometer (Shimadzu UV-2600i). The transmittance data are as follows: Fig. 9 shown.

[0097] Through the light transmittance test data of F16-F21, it can be concluded that: under the same mixing ratio, the combination of a polymer material based on MS (styrene-methyl methacrylate copolymer) with a more prominent interface effect and another interface effect resin has a more prominent light-blocking performance compared to the combination of any other two polymer materials with weaker interface effects. Therefore, when designing a light-blocking formula, MS (styrene-methyl methacrylate copolymer) should be used as the main mixing body.

[0098] Comparing the light transmittance test data of F22-F25, it can be seen that the light blocking property of the mixture of three or more polymers with interface effect based on MS (styrene-methyl methacrylate copolymer) (average transmittance 4.91%) is close to the light blocking property of the mixture of two polymer materials with interface effect based on MS (styrene-methyl methacrylate copolymer) (average transmittance 4.74%), and is even slightly worse than the light blocking property of the mixture of two polymer materials with effect based on MS. The F23 (MS: TPE: PMP: POK = 3.5:2:1.5:1) sheet was scanned by electron microscope (such as Fig.10 As shown), the electron microscope is CIQTEK SEM5000.

[0099] Based on electron microscopic analysis, the applicant believes that the resins with multiple interface effects are accumulated in the PET base resin, and the interface effects and microbubble structures of the single material itself are mutually influenced or superimposed to amplify into a more obvious broken interlayer structure, which makes it easier for light to penetrate, thereby weakening its positive interface light blocking performance to a certain extent. In addition, the production and processing of a mixture of two polymer materials is more convenient than the mixed processing of three or more polymer materials with different proportions.

[0100] Furthermore, different polymers and polyester materials may have poor compatibility problems under specific ratios or specific processing conditions, which may lead to delamination of the film wall after injection molding or bottle blowing or a decrease in the physical properties and toughness of the bottle. It can be considered to add a compatibilizer or grafting agent to improve the compatibility of the polymer and polyester plastic. These compatibilizers or grafting agents include but are not limited to POE grafted glycidyl methacrylate (POE-g-GMA), polypropylene grafted maleic anhydride (PP-g-MAH), polyethylene grafted maleic anhydride (PE-g-MAH), POE grafted maleic anhydride (POE-g-MAH), etc. Experiments show that adding a lower proportion (such as 0.5% to 2%) of the compatibilizer has little effect on the light-blocking performance of the bottle, but can improve the elongation at break of the mixture and improve the flexibility. The specific test data are shown in Table 8 below:

[0101] Table 8

[0102]

[0103] Because styrene-methyl methacrylate copolymer alone or in combination with other polymers in a specific proportion has an obvious interfacial light-blocking synergistic effect, the amount of titanium dioxide used for light blocking in the light-blocking masterbatch formula can be significantly reduced. At the same time, in order to improve the light-blocking performance, other metal pigments with high hiding power (metallic aluminum pigments or bronze fragments) and other high-hiding inorganic substances that can play a steric hindrance role can be combined, such as calcined kaolin, calcite powder, silica powder, zinc oxide, barium sulfate, zinc sulfide, calcium carbonate or pearlescent mica, etc., as well as other fillers with covering effects: metal oxide particles; specifically including: iron oxide red (PR 101), iron oxide black (PBlk 11), chrome green-black hematite (PG 17), cobalt aluminate (PB 28) or aluminum trihydrate (Al(OH)3), etc.

[0104] The steric hindrance effect is also called the stereo effect, which mainly refers to the steric hindrance caused by the proximity of extremely small particles or molecular groups. In order to achieve the ideal light-blocking and whiteness effects, in the light-blocking masterbatch formula based on styrene-methyl methacrylate copolymer, it is necessary to consider minimizing the amount of titanium dioxide. Usually, the content of titanium dioxide (preferably rutile titanium dioxide) in the formula does not exceed 50%. According to specific requirements, it can be no more than 40%, or even no more than 30%. With a specific proportion of metal pigments and other inorganic fillers, it can also achieve excellent light-blocking effects and maintain higher whiteness and processing performance.

[0105] In order to facilitate the processing and production of light-blocking masterbatch and improve the dispersibility and processing performance, dispersants or internal and external lubricants should be added during granulation, including but not limited to polyethylene wax, EVA wax, monopolyester wax, stearate glycerol GMS, stearates (such as calcium stearate, magnesium stearate, zinc stearate, etc.), amide wax (vinyl bisstearamide EBS, erucamide, oleamide, etc.), pentaerythritol stearate PETS, etc. The introduction of wax will also have a positive effect on the light-blocking performance.

[0106] In addition, according to the final application requirements, pigments or organic dyes are directly added to the light-blocking masterbatch formula to improve whiteness or present a colorful light-blocking effect. These pigments or dyes include but are not limited to the following red, yellow and blue primary colors of organic or inorganic substances, as shown in Table 9 below:

[0107] Table 9

[0108]

[0109]

[0110] Based on these commonly used pigments or dyes, colorful high-light-blocking bottles that meet production requirements can be produced, thereby increasing consumers' association and recognition of the food and beverages in the packaging bottles.

[0111] In addition, according to the production and terminal application requirements, other functional additives are added in this embodiment to improve the quality and stability of the bottle or the contents.

[0112] Antioxidants are added, including but not limited to high molecular weight hindered phenol antioxidants, solid organic phosphite antioxidants, etc.

[0113] Add additives that can improve the re-absorption performance of polyester, such as carbon black, tungsten oxide, activated carbon, titanium nitride, zinc nitride, etc.

[0114] Add light stabilizers such as UV234, UV1577, UV1164, UV360, UV3638, etc.

[0115] It also includes antistatic agents such as cationic surfactants or anionic surfactants.

[0116] According to the idea of ​​the invention of this application, the corresponding raw materials were purchased from the market to produce the following groups of experimental examples:

[0117] Experimental Example 1: Styrene-methyl methacrylate copolymer MS (TX400S from Nippon Electric Chemical) 25%, thermoplastic polyester elastomer TPEE (DuPont TPEE 4556) 25%, titanium dioxide (Chemours R-902) 35%, metal aluminum paste (ECKARTMASTERSAFE MP100-20B) 2%, barium sulfate (SAKAI BARIACE B-34) 11% and auxiliary agents such as polyester wax / antioxidant (SI Group) 2%.

[0118] Experimental Example 2, styrene-methyl methacrylate copolymer MS (Nippon Electric Chemical TX400S) 30%, thermoplastic polyester elastomer TPEE (DuPont TPEE 4556) 20%, titanium dioxide (Chemours R-902) 35%, metal aluminum paste (ECKARTMASTERSAFE MP100-20B) 2%, barium sulfate (Sakai Chemical BARIACE B-34) 11% and auxiliary agents such as polyester wax / antioxidant (Saikote) 2%.

[0119] Experimental Example 3, styrene-methyl methacrylate copolymer MS (Nippon Electric Chemical TX400S) 40%, thermoplastic polyester elastomer TPEE (DuPont TPEE 4556) 10%, titanium dioxide (Chemours R-902) 35%, metal aluminum paste (ECKARTMASTERSAFE MP100-20B) 2%, barium sulfate (Sakai Chemical BARIACE B-34) 11% and auxiliary agents such as polyester wax / antioxidant (Saikote) 2%.

[0120] Experimental Example 4, styrene-methyl methacrylate copolymer MS (TX400S from Nippon Electric Chemical) 35%, PMMA (IH830 from LG Chemical) 10%, titanium dioxide (Chemours R-902) 35%, metal aluminum paste (ECKART MASTERSAFE MP100-20B) 2%, barium sulfate (SAKAI BARIACE B-34) 11% and auxiliary agents such as polyester wax / antioxidant (SI Group) 2%.

[0121] Experimental Example 5, thermoplastic polyester elastomer TPEE (DuPont TPEE 4556) 35%, PMMA (LG Chemical's IH830) 15%, compatibilizer (POE-g-MAH, Mitsui Chemicals MH5020) 1.5%, titanium dioxide (Chemours R-902) 37%, metal aluminum paste (ECKART MASTERSAFE MP100-20B) 1.5%, zinc oxide (Lutai LT-AH01) 8% and auxiliary processing aids such as stearate / UV stabilizer (BASF) 2%.

[0122] Experimental Example 6, polymethylpentene PMP (Mitsui Chemicals TPXRT180) 35%, PMMA (LG Chemicals IH830) 15%, compatibilizer (POE-g-MAH, Mitsui Chemicals MH5020) 1.5%, titanium dioxide (Chemours R-902) 37%, metal aluminum paste (ECKARTMASTERSAFE MP100-20B) 1.5%, zinc oxide (Lutai LT-AH01) 8% and auxiliary processing aids such as stearate / UV stabilizer (BASF) 2%.

[0123] Experimental Example 7, styrene-methyl methacrylate copolymer MS (Nippon Electric Chemical TX400S) 40%, polymethylpentene PMP (Mitsui Chemicals TPXRT180) 10%, compatibilizer (PP-g-MAH, Arkema 18732) 1%, titanium dioxide (Chemours R-902) 39%, metal aluminum paste (ECKART MASTERSAFE MP100-20B) 1%, calcined kaolin (BASF Translink37) 7%, monoglyceride GMS / EBS wax and other processing aids (Honeywell) 1.8% and ultramarine pigment (Holliday 5012) 0.2%.

[0124] Experimental Example 8, styrene-methyl methacrylate copolymer MS (TX400S from Nippon Electric Chemical) 40%, cycloolefin copolymer COC (Polyplastics 6013S from Japan) 10%, compatibilizer (PP-g-MAH, Arkema 18732) 1%, titanium dioxide (Chemours R-902) 39%, metal aluminum paste (ECKART MASTERSAFE MP100-20B) 1%, calcined kaolin (BASF Translink37) 7%, monoglyceride GMS / EBS wax and other processing aids (Honeywell) 1.8% and ultramarine pigment (Holliday 5012) 0.2%.

[0125] Experimental Example 9, styrene-methyl methacrylate copolymer MS (TX400S from Japan Electric Chemical) 40%, aliphatic polyketone POK (M630 from Korea Hyosung) 10%, compatibilizer (PP-g-MAH, Arkema 18732) 1%, titanium dioxide (Chemours R-902) 39%, metal aluminum paste (ECKART MASTERSAFE MP100-20B) 1%, calcined kaolin (Translink37 from BASF) 7%, monoglyceride GMS / EBS wax and other processing aids (Honeywell) 1.8% and ultramarine pigment (Holliday 5012) 0.2%.

[0126] Production process:

[0127] All the materials in the above experimental examples are mixed in a closed hydraulic constant pressure mixer or dispersed into a uniform mixture at high speed in a high speed mixer, and then directly added to a temperature-controlled twin-screw extruder for granulation. The main process is: plasticization, vacuuming, extrusion, air cooling or water cooling, air drying, cutting, screening particles on a vibrating screen with air blowing, dehumidification and drying, and then weighing and packaging. For a small amount of granular or powder materials, they can also be added in the corresponding proportion through a side feeding device. In a production embodiment of the present invention, the typical process values ​​are set as follows: 1. The extruder screw section is set as the feed temperature section: 280℃~290℃, the equilibrium temperature section: 270℃~280℃, and the discharge temperature section: 260℃~270℃; the side feeding zone is the equilibrium temperature zone: 260℃; the vacuum degree of the vacuum section is controlled at 0.6~0.8Mpa; the extrusion section temperature: 260℃; circulating cooling water cooling; three-stage blower air drying method; pelletizer speed: 800~900r / min; vibration screen uniform particles, water centrifugal separation and drying; dehumidification and drying; metering, weighing and packaging.

[0128] For the above nine groups of experimental examples, as well as conventional high-light-blocking masterbatch (Hanhui LBS-1, with a formula of 30% PET as the base resin, including about 70% titanium dioxide, metal pigments and inorganic components such as carbon black), after drying at 90°C for 2 hours, the above ten groups of samples were all added at a mass unit ratio of 10%, with 90% bottle-grade polyester chips (Zhejiang Wankai WK-801, dried at 170°C for 6 hours), injection molded into bottle embryos (injection molding machine: Zhenxiong EM120-SVP), and blown into bottles (blowing machine: Langs LS-T12), and bottle wall slices of about 4cm×4cm with a thickness of 0.26mm were cut and their whiteness was tested using KONICA MINOLTA chromatograph CM-3700A. The test results are shown in Table 10 below:

[0129] Table 10

[0130]

[0131] In addition, combined Fig.11 From the data in Table 10, it can be seen that the whiteness of the bottle prepared based on the scheme of the present invention is significantly improved compared with the whiteness of the bottle of the traditional high light-blocking masterbatch.

[0132] Compare the light-blocking properties of PET bottles blown by the above ten groups of samples. Take three sample bottles from each group, cut a 2.5cm×5cm thin slice of 0.3mm thickness from the same part, and use the Shimadzu UV-2600i spectrophotometer with an integrating sphere to test the light transmittance. Select the curves in the middle or overlapping of the three sample slices in each group. The comparison results are as follows: Fig.12 shown.

[0133] Fig.12 It can be clearly seen that the light-blocking scheme based on the invention of this application has significantly improved light-blocking performance compared to the traditional high light-blocking masterbatch at the same addition ratio. In particular, styrene-methyl methacrylate copolymer MS and aliphatic polyketone POK, cycloolefin copolymer COC or polymethylpentene PMP have better light-blocking performance. This is the test data obtained when the titanium dioxide content in the bottle (between 3.5% and 4%) is about half of the traditional light-blocking masterbatch (titanium dioxide content in the bottle is about 7%).

[0134] Because the invention of the present application has better compatibility with polyester PET and is easier to be evenly dispersed with the molten polyester in the screw of the injection molding machine, the injection temperature of the preform can be appropriately reduced by 3-5°C compared with the traditional high-light-resistance masterbatch during embryo injection, especially in the first and second stages of injection molding, it can even be reduced by 5-8°C, which significantly saves processing energy consumption, improves the yield of the preform to a certain extent, and also improves the size and appearance of the preform, such as pinholes, tailing, flash, stress distribution, etc. to varying degrees.

[0135] In terms of bottle blowing, the present invention is easier to blow-form, the bottle blowing process window is wider, the molding is better, the foot standing surface is fuller at all angles, the pre-blowing time and pressure can be appropriately reduced, and the bottle body pressure is more stable. Compared with Experimental Example 2 in the present invention and the traditional high-resistance masterbatch (Hanhui LBS-1), both are blown at a 10% addition ratio. 21 grams and a volume of 350ml container bottles are compared. The vertical pressure of the empty bottle is compared. The two groups of comparison effects are as follows Fig.13 - Fig.14 shown.

[0136] Specifically, weigh the masterbatch made in Experimental Example 2 of this application according to a 10% ratio, blend it evenly with 90% of dried polyester PET (Wankai WK-801), and then blow-blow it. Take 10 bottles as sample bottles and mark them as 1-10; weigh 10% of traditional light-blocking masterbatch (LBS-1, a commercial product of Hanhui), blend it with 90% of dried polyester PET (Wankai WK-801), and then blow-blow it. Take 10 bottles as control bottles and mark them as 1-10. Use Alpha Vertical Load-Bearing Tester XLW-B to conduct empty bottle vertical load-bearing test on the above two groups of samples. The load-bearing yield curve and load-bearing stability curve are shown in the figure. Fig.13 - Fig.14 shown.

[0137] from Fig.13 - Fig.14 It can be seen from the two comparison curves that Experimental Example 2 based on the present invention has a higher yield and a more stable pressure bearing capacity under empty bottle pressure, which also shows that the bottle based on Experimental Example 2 of the present invention has better strength and toughness.

[0138] Weigh 10% of the masterbatch made in Experimental Example 2, blend it with 90% of the dried polyester PET (Wankai WK-801) and then blow the preforms. Take 8 bottles as sample bottles, fill them with water and tighten the lids. Label the sample bottles as sample bottles 1-8; weigh 10% of the traditional light-blocking masterbatch (LBS-1, a commercial product of Hanhui), blend it with 90% of the dried polyester PET (Wankai WK-801) and blow the preforms. Take 8 bottles as control bottles, fill them with water and tighten the lids. Label the control bottles as control bottles 1-8. Use Zhuyan anti-drop tester BFI-20 to carry out drop test, using two drop test conditions of 1.4m / 4℃ and 1.4m / 4℃ / 30kPa. Each condition tests the vertical drop and horizontal drop of each bottle. The test results are shown in Table 11 below.

[0139] Table 11

[0140]

[0141] Based on sample bottles 1-8, all the drop tests passed; while the bottles based on traditional high-light-blocking masterbatch all passed the test under the conditions of 1.4m / 4℃, but under the pressure of 1.4m / 4℃ / 0.3bar, there were different proportions and degrees of deformation of the bottles in both vertical and horizontal drops. It can be seen from the above tests that the toughness and strength of the bottles in Experimental Example 2 of the present invention have been improved to a certain extent.

[0142] In order to compare the energy consumption of blowing bottles between the examples of the present invention and the traditional high light-blocking masterbatch, the blowing bottle process was verified (blowing machine: Sidel SBO 2 / / 10 10433). After the blowing bottle process was adjusted and stabilized, the blowing bottle temperature setting of the present invention was lower than that of the traditional light-blocking masterbatch. The blowing bottle temperature could be reduced by about 5°C on average, from 128°C, the commonly used blowing bottle temperature of the traditional light-blocking masterbatch, to 123°C. The blowing bottle energy consumption was reduced by 4%, ((128-123) / 128=4%). This is because styrene-methyl methacrylate copolymer or a mixture of styrene-methyl methacrylate copolymer and other resins in corresponding proportions has better fusion, fluidity and dispersibility in PET polyester, and is easier to blow into bottles, so the blowing bottle pressure and blowing temperature can be reduced to a certain extent during blowing.

[0143] According to the above blowing energy consumption comparison test, the 4% saving, the annual use of 1 million tons of polyester chips with high light-blocking additives for dairy packaging, the empirical value of 230 kWh of energy consumption for blowing bottles per ton of polyester light-blocking preforms (the power consumption of different blowing equipment may be different, the data here is only for example), the electricity fee of 1 yuan / kWh (refer to the average industrial electricity fee on the market), and 1 kWh of electricity consumption is equivalent to 0.997 kg of CO2 emissions (based on the data of the Carbon Emission Trading Network). The use of the invention scheme of this application can save more than 90 million yuan in electricity bills and reduce more than 9,000 tons of carbon emissions in a year. The data is shown in Table 12, and the energy consumption savings in the injection molding stage are not even calculated.

[0144] Table 12

[0145]

[0146] Embodiment 2

[0147] In addition, this embodiment also provides a method for preparing a high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch, which is used to prepare the light-blocking masterbatch in Example 1, comprising the following steps:

[0148] Disperse the formulated materials into a uniform mixture and granulate them.

[0149] The granulation process comprises:

[0150] The mixture is heated to the plasticizing temperature and vacuumed;

[0151] Passing the plasticized material through an extruder to form a continuous molten extrudate;

[0152] Cooling to form solid particles;

[0153] The solid particles are cut into predetermined sizes and then screened and discarded.

[0154] Furthermore, during the granulation process, the feed temperature section is set at 280°C to 290°C, the equilibrium temperature section is set at 270°C to 280°C, and the discharge temperature section is set at 260°C to 270°C.

[0155] The vacuum degree of the vacuum pumping section is controlled at 0.6-0.8Mpa; the temperature of the extrusion section is 260°C; the speed of the pelletizer is 800-900r / min.

[0156] Specifically, the method may include the following specific steps:

[0157] All materials in the formula are mixed in a closed hydraulic constant pressure mixer or dispersed into a uniform mixture at high speed in a high speed mixer, and then directly added to the temperature controlled twin screw extruder for granulation. The main process is: plasticization, vacuuming, extrusion, air cooling or water cooling, air drying, cutting, screening particles on a vibrating screen with air blowing, dehumidification and drying, and then weighing and packaging. For a small amount of granular or powder materials, they can also be added in the corresponding proportion through the side feeding device.

[0158] In a specific production embodiment of the present invention, the typical process values ​​are set as follows: 1. The extruder screw section is set as the feed temperature section: 280℃~290℃, the equilibrium temperature section: 270℃~280℃, and the discharge temperature section: 260℃~270℃; the side feeding zone is the equilibrium temperature zone: 260℃; the vacuum degree of the vacuum section is controlled at 0.6~0.8Mpa; the extrusion section temperature: 260℃; circulating cooling water cooling; three-stage blower air drying method; pelletizer speed: 800~900r / min; vibration screen uniform particles, water centrifugal separation and drying; dehumidification and drying; metering, weighing and packaging.

[0159] The present invention also provides a production line for high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch, comprising: an internal mixer or a high-speed mixer, an extruder, a blower, a pelletizer and a dehumidifying and drying device.

[0160] The internal mixer or high speed mixer is used to disperse the materials into a uniform mixture, the extruder is used to granulate the mixture, and the dehumidification and drying device is used to dehumidify and dry the granules.

[0161] Furthermore, the extruder also includes an air blowing device and a pelletizing device, wherein the air blowing device is used to dry the plasticized and extruded material, and the pelletizing device is used to cut the dried material into pellets.

[0162] In summary, the scheme of the present invention selects styrene-methyl methacrylate copolymer as the basic carrier, and the styrene-methyl methacrylate copolymer is blended with polyester plastic to form an uneven and irregular interface effect during the stretching process of blowing and injection molding, which scatters, refracts and reflects light, reduces the transmittance of light, and thus achieves a synergistic light-blocking effect; in order to maximize the interface effect, in addition to styrene-methyl methacrylate copolymer, a polymer that also has a certain interface effect with polyester plastic is added; at the same time, a compatibilizer or a grafting agent is added to improve the compatibility of the polymer and polyester plastic; under the same addition ratio, the light-blocking masterbatch disclosed by the present invention has higher whiteness and light-blocking properties, lower titanium dioxide content, and the energy consumption of injection molding and blowing can be significantly reduced, and the physical properties of the bottle body are better, the toughness effect is better, and the cost is lower.

[0163] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch, characterized in that: include: Styrene-methyl methacrylate copolymer resin, thermoplastic polymer material and titanium dioxide; The mass content of the styrene-methyl methacrylate copolymer resin is 5% to 60%, the mass content of the thermoplastic high polymer material is 3% to 30%, and the mass content of the titanium dioxide is 10% to 60%; The thermoplastic high polymer material includes: one or more of thermoplastic elastomer TPE, polymethyl methacrylate PMMA, poly-4-methyl-1-pentene PMP, cycloolefin copolymer COC, thermoplastic polyester elastomer TPEE or aliphatic polyketone resin POK.

2. The high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 1, characterized in that: It also includes high-hiding inorganic substances with a mass content of 1% to 30%, wherein the high-hiding inorganic substances include one or more of calcined kaolin, calcite powder, silicon powder, zinc oxide, barium sulfate, zinc sulfide or calcium carbonate.

3. The high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 1, characterized in that: The invention also comprises a metal pigment with a mass content of 0.01% to 5%, wherein the metal pigment comprises a metal aluminum pigment or a bronze pigment.

4. The high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 1, characterized in that: The invention also comprises a compatibilizer with a mass content of 0.01% to 5%, wherein the compatibilizer comprises one or more of POE-g-GMA, PP-g-MAH, PE-g-MAH or POE-g-MAH.

5. The high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 1, characterized in that: The invention also comprises an auxiliary agent with a mass content of 0.01% to 10%, wherein the auxiliary agent comprises one or more of a dispersing lubricant, an antioxidant, a re-absorbent, a light stabilizer or an antistatic agent.

6. The high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 1, characterized in that: It also includes organic dyes with a mass content of 0.01% to 10%.

7. A method for preparing a high-whiteness, low-titanium dioxide content, high-efficiency light-blocking masterbatch, used for preparing a high-whiteness, low-titanium dioxide content, high-efficiency light-blocking masterbatch as claimed in any one of claims 1 to 6, characterized in that: include: Disperse the formulated materials into a uniform mixture for granulation; The granulation process comprises: The mixture is heated to the plasticizing temperature and vacuumed; Passing the plasticized material through an extruder to form a continuous molten extrudate; Cooling to form solid particles; The solid particles are cut into predetermined sizes and then screened and discarded.

8. The method for preparing a high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 7, characterized in that: During the granulation process, the feed temperature section is set at 280°C to 290°C, the equilibrium temperature section is set at 270°C to 280°C, and the discharge temperature section is set at 260°C to 270°C.

9. The method for preparing a high-whiteness and low-titanium dioxide content high-efficiency light-blocking masterbatch according to claim 7, characterized in that: In the granulation process, the vacuum degree of the vacuum pumping section is controlled to be 0.6-0.8 MPa; the temperature of the extrusion section is 260° C.; and the speed of the pelletizer is 800-900 r / min.

Citation Information

Patent Citations

  • Shading modified plastic, preparation method and application thereof

    CN111793330A

  • Shading master batch based on low titanium dioxide content and preparation method thereof

    CN113583397A

  • Light-blocking master batch, bottle preform raw material composition containing light-blocking master batch, bottle preform and bottle

    CN113929931A

  • Composites with good mechanical and tribological properties, useful e.g. for injection molding, comprise fine titanium dioxide particles in (thermo)plastic and / or epoxy resin matrix

    DE102007040638A1

  • Polyester packaging material

    US20200399463A1